PARTISIPASI MASYARAKAT DALAM PROSES PERENCANAAN RKP DESA (STUDI KASUS DESA BAYEUN KECAMATAN RANTAU SELAMAT KABUPATEN ACEH TIMUR) - Mohd Rizki Maulana; muhammad Abrar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis study aims to determine the participation of the Bayeun Village community in planning, to determine the participation of the Bayeun Village community in the implementation, to determine the participation of the Bayeun Village community in Utilization, and to determine the participation of the Bayeun Village community in the Evaluation. This research was conducted in Bayeun Village, Rantau Selamat District, East Aceh Regency. The method used is descriptive qualitative and quantitative methods with crosstab analysis. The number of respondents in this study was 10 respondents who were obtained through observation, interviews and documentation with a sampling technique with certain considerations (purposive sampling). The results showed that there was planning participation in the process of preparing the Village RKP obtained 17,083 with a sig of 0.030, the implementation participation in the process of preparing the RKP Desa was obtained 15,972 with a sig of 0.013, the participation of utilization in the process of preparing the RKP Village was obtained 4,167 with a sig of 0.002, and the existence of evaluation participation in the process of preparing the Village RKP obtained 7,778 with a sig of 0.005.enKeywords: Biodiesel Consumption in Indonesia.